Men’s Experiences of Psychological and Other Forms of Abuse in Intimate Relationships: A Qualitative Study - Gloria Macassa; Frida Stål; Michelle Rydback; Joan Pliakas; Daniel Winsjansen; Anne-sofie Hiswåls; Joaquim Soares (Societies, 2025)
Intimate partner violence (IPV) is a public health and social problem worldwide. However, most studies have concentrated on violence against women and not also against men. Interventions for victimized men will only be successful if there is a better understanding of the real experiences, as narrated by the victims themselves, and how these impact their health and wellbeing. This study aimed to investigate the experiences of intimate partner violence, health, and wellbeing among men in east-central Sweden. Data were gathered using eleven in-depth, semi-structured interviews with men who were victims of IPV. Four categories emerged from the analyses: experiences of abuse in the relationship; feelings of isolation, loneliness, and shame; perceived deterioration of health and wellbeing; and negative experiences with public services. The findings indicate that interviewees experienced psychological (rather than physical) violence at the hands of their intimate partner. The abuse had consequences for their health and wellbeing, as they experienced stress, anxiety, depression, and suicidal thoughts. In some instances, it affected their health behavior, as they reverted to alcohol and drug use to cope with the abuse. Moreover, the interviewees felt lonely and unwilling to disclose their suffering because of fear of what family, friends, society, and professionals across different services would think of them. Also, they experienced negative responses from the health and social care services and police when seeking help, which made them even more entrenched in their fear of disclosing the suffering caused by the abuse.